Rights of the future generations or Duties of the present generations? – Justice and Responsibility under the lens of the climate change (BioLaw Journal - Rivista di BioDiritto, 2023)
Climate change is forcing philosophical and legal thought to recompose the complexity of a polycentric phenomenon and highlight the break with traditional concepts. The explosion of climate change litigation is an opportunity to examine the intergenerational instance in the justice and civil liability. The simplicity with which future generations have entered the constitutional charters does not correspond to the possibility of configuring individual legal rights in the dynamics of private law. The impossibility of drawing effective and actionable defense for individuals reveals the weakness of known remedies in the presence of contemporary activity that falls negatively on the future community.
Keywords: Climate justice; Tort Law; future generations; climate change; sustainability